Ionic Liquids Catalysis for Carbon Dioxide Conversion With Nucleophiles - Xia, Shu-Mei; Chen, Kai-Hong; Fu, Hong-Chen; He, Liang-Nian (Frontiers in Chemistry, 2018)
Carbon dioxide, as a promising C1 synthon, has attracted great interest in organic synthesis. Due to the thermodynamic stability and kinetic inertness of CO2, developing efficient strategies for CO2 activation and subsequent conversion from is very crucial. In this context, Ionic liquids (ILs) show great potential for capturing and activating CO2 owing to their unique structures and properties, making them become ideal alternatives to volatile organic solvents and/or catalysts for CO2 transformation. This minireview aims at summarizing ILs-promoted reactions of CO2 with nucleophiles. Two catalytic systems i.e. metal/ILs dinary systems such as Cu/ILs systems and Ag/ILs systems as well as single ILs systems including anion-functionalized ILs and dual-functionalized ILs have been developed for CO2 catalytic transformations, for instance, carboxylative cyclization of nucleophiles e.g. propargylic alcohols, amines, 2-aminobenzonitriles and o-aminobenzenethiol, and formylation of amines or 2-aminothiophenols with hydrosilanes to afford various value-added chemicals e.g. cyclic carbamates, unsymmetrical organic carbonates, α-hydroxyl ketones, and benzimidazolones. In a word, IL could provide a powerful tool for an efficient CO2 utilization.